Brain Mapping Project: Clinical Aspects and Role of Neuroradiology - Levy, L.M. (American Journal of Neuroradiology, 2013)
SUMMARY: As experts in the realm of applying brain imaging technology for meaningful information on an individual patient's medical care, neuroradiologists can provide a physiologic, pathophysiologic, and clinical context for the advances achieved from brain-mapping. Precise identification of the abnormalities involved in brain conditions resulting from a multidisciplinary effort including neuroradiology will help to further define the nature of the pathology, evaluate the results of therapy, and improve health care.